Intraluminal impedance: electromagnetic modeling, signal analysis, and computer assisted diagnosis of gastroesophageal reflux - Al-Zaben, Awad, author; Chandraeskar, V., advisor; Bringi, V., committee member; Lile, Derek, committee member; Wheeler, Donna, committee member (Colorado State University. Libraries, 2003)
Multichannel intraluminal impedance modeling and analysis research consists of two parts as in any remote sensing problem namely: a) The forward problem that models the process, and b) The inverse problem of signal analysis and extraction. The low frequency electric field in the human body resulting from the injection of a constant current is described by Laplace's equation. In multichannel intraluminal impedance the problem is further complicated by the varying impedance of bolus and multiple layers in the esophagus. Numerical technique used to model the forward problem in order to establish the feasibility of this procedure for monitoring the esophagus. Various conditions of the esophagus are considered. Both normal and diseased situations are modeled. Biomedical problems are typically fairly complex and the biomedical measurements such as the multiple intraluminal impedance varies widely due to the change of various factors including internal factors such as acid reflux, bolus swallow and external factors such as respiration and patient movement. An analytical technique to study the impedance signals, detect gastroesophageal reflux episodes as well as their classification is developed and presented in this dissertation.
Keywords: biomedical research; biomedical engineering